Psicanálise e religião - Argelazi, Patricia Leirner (2008)
The objective of this work is to review the principle texts of Freud which treat the subject of religion and to propose a map with which to study his ideas striving, whenever possible, to discriminate Freud's important contributions from his radically anti-religious militancy. This work also makes a discussion if the psychoanalytical theory is compatible with religion. This study also includes the influence of two important interlocutors , the preacher Oskar Pfister and the writer Romain Rolland. And to finalize, the work briefly presents some relevant considerations of Winnicott. The study concludes that Freud s own scientific account became restricted by his prejudicial view of religion